Bigels—oleocolloid matrices—as probiotic protective systems in yogurt. Issue 11 (12th October 2021) - Zhuang, Xiaoqing; Clark, Stephanie; Acevedo, Nuria
Abstract : Abstract: The probiotic yogurt market is strong because of the potential benefits that probiotics provide to the host, such as relieving lactose intolerance symptoms, easing diarrhea, and improving the immune system. However, probiotics are sensitive to processing conditions and the high acidity of yogurt can reduce survival of probiotics and limit yogurt shelf life. Here, oleocolloid technology (bigels) was used to improve the survival of probiotics during yogurt shelf life. Bigels are semisolid systems containing a polar and a non‐polar phase mixed forming a material with improved properties. Probiotic bigels were prepared by mixing a soy lecithin‐stearic acid oleogel emulsion and a whey protein hydrogel, followed by the incorporation of Lactobacillus acidophilus and Bifidobacterium lactis suspended in milk. Yogurt was prepared with 18% wt/wt probiotic bigels with (Swiss‐style) and without (sundae‐style) agitation. Probiotic viability was monitored for 6 weeks. The total counts of L. acidophilus and B. lactis entrapped in bigels were significantly higher than free bacteria in yogurt after 3 and 5 weeks, respectively, indicating that probiotics could be entrapped and their survival enhanced. Both yogurt styles showed a meant total count of 3.3 and 4.5 log CFU/g for L. acidophilus and B. lactis, respectively at the end of storage time suggesting that despite agitation of yogurt, bigel structure played a key role in protecting probiotic viability.